Fluoroless endourological surgery for high burden renal and proximal ureteric stones: A safe technique for experienced surgeons. Issue 4 (2nd October 2021) - Ayoub, Elias M.; Bourgi, Ali; Alsouki, Josee; Merhej, Sleiman; Conort, Pierre
ABSTRACT: Objective : To describe the feasibility of treating proximal ureteric and renal stones using flexible ureteroscopy (fURS) or a double approach (mini-percutaneous nephrolithotomy [PCNL] + fURS) without any use of radiation. Patients and methods : We retrospectively reviewed the data of all patients operated by one surgeon for retrograde endoscopic removal of renal and ureteric lithiasis performed between June 2015 and January 2019 in our institution. Patients with anatomical complexities, high-burden stone disease (diameter >20 mm), and medical comorbidities (anti-platelet drug administration) were included in our study. Outcomes analysed included complication rate, stone-free rate (SFR, defined as no residual stone >1 mm), and repeat procedure rate. Results : In all, 183 consecutive URS for proximal ureteric and renal lithiasis were conducted. C-arm fluoroscope guidance was not required, not even in the complex cases. Simultaneous ultrasonography and fURS guidance was used in patients where the mini-PCNL approach was indicated. Lead aprons were not needed by the operating room staff in any of the operations. The SFR was 91.8% after the first procedure, with no Clavien–Dindo Grade III or IV complications. Conclusion : Our present series shows clearly that the fURS and mini-PCNL approach under fURS control is a feasible and safe technique for experienced surgeons. Patients had a high SFR and no technique-related complications, with no additional risk of X-ray exposure. However, a prospective study is required to test the reproducibility of this technique. Abbreviations : GMSV: Galdakao-modified supine Valdivia; ICRP: International Commission on Radiological Protection; KUB: plain abdominal radiograph of the kidneys, ureters and bladder; OR: operating room; PCNL: percutaneous nephrolithotomy; SFR: stone-free rate; UAS: ureteric access sheath; (f)URS: (flexible) ureteroscopy; US: ultrasonography